Emerging Understanding of the Mechanism of Action for Dimethyl Fumarate in the Treatment of Multiple Sclerosis - Mills, Elizabeth A.; Ogrodnik, Magdalena A.; Plave, Andrew; Mao-Draayer, Yang (Frontiers in Neurology, 2018)
Dimethyl fumarate (DMF) is an effective treatment option for relapsing-remitting multiple sclerosis (MS), but its therapeutic mechanism of action has not been fully elucidated. A better understanding of its mechanism will allow for the development of assays to monitor its clinical efficacy and safety in patients, as well as guide the development of the next generation of therapies for MS. In order to build the foundation for determining its mechanism, we reviewed the manner in which DMF alters lymphocyte subsets in MS patients, its impact on clinical efficacy and safety, as well as its molecular effects in cellular and animal models. DMF decreases absolute lymphocyte counts, but does not affect all subsets uniformly. CD8+ T-cells are the most profoundly affected, but reduction also occurs in the CD4+ population, particularly within the pro-inflammatory T-helper Th1 and Th17 subsets, creating a bias toward more anti-inflammatory Th2 and regulatory subsets. Similarly, B-lymphocyte and Natural Killer populations are also shifted toward a more anti-inflammatory state. In vitro and animal models demonstrate a role for DMF within the central nervous system (CNS) in promoting neuronal survival in an Nrf2 pathway dependent manner. However, the impact of DMF directly within the CNS of MS patients remains largely unknown.